Principals Leadership Styles and Students’ Academic Performance in Enugu Metropolis: A Comparative Survey of Public and Mission Secondary Schools - Igwe, Nicholas N.; Ndidiamaka M., Ozofor; Chidi, Alinno Francis (Archives of Business Research, 2017)
Education is a fundamental human right enshrined in all major United Nations and International Charters. As a result, there is need to provide it in most efficient manner. Education plays a major role in social emancipation, political, economic and cultural development of countries. However, the low performance of teachers and its negative impact accentuated by the dwindling fortunes of students’ academic performance have become a great concern to major stakeholders in the education sector. The study compares the leadership styles of principals in public and mission secondary schools on students’ academic performance in Enugu South Local Government Area of Enugu State, Nigeria. Ex-post facto descriptive research design was adopted. Data collection instruments were the use of structured questionnaire and interviews. The Yamane’s (1964) statistical formula was used for sample size determination. A total of 285 copies of the questionnaire were administered to principals, teachers and supportive staff of the selected Secondary Schools using simple random sampling techniques. A combination of chi-square and Pearson product moment correlation statistical tools at 0.05 level of significance was utilized. Results of the investigation reveal that autocratic leadership style was positively correlated with students’ academic performance. The study recommends that the application of autocratic leadership style by principals has the capacity of increasing the level of students’ academic performance.